Looking Backward Instead of Forward: Aspiration-Driven Influences on the Efficiency of the Capital Allocation Process - Arrfelt, Mathias; Wiseman, Robert M.; Hult, G. Tomas M. (Academy of Management Journal, 2013)
This study examines the influence of backward-looking, reference-dependent decisions on forward-looking capital allocation investment choices across business units within a firm. Specifically, we develop an integrated behavioral framework for predicting how aspirations for business unit performance affect the efficiency of the internal capital allocation process. Results suggest that, contingent on dispersion in business unit performance and on firm slack, performance aspirations have pervasive effects; current performance above and below aspirations influences the efficiency of the allocation process. Given that prior examinations of aspiration-driven behavior have generally focused on changes in strategic organizational actions (e.g., R&D investment) without further considering the quality or appropriateness of such actions, this study contributes by also focusing on the appropriateness of capital allocations with clear implications for allocation efficiency.